The perceived relationship between the shareholder primacy and the non-service of the bottom of the range pyramid market (BOP) - Moloi, Tsele Phillip (My University, 2014)
The problems of poverty and other complex challenges society is facing has been a front burner issue in development discourse around the world. The limitations that multilateral and aid agencies are facing in addressing these issues have called for the involvement of business as creators of wealth to bring forth their capabilities and business core competencies in helping address these complex problems of our time. This market based solution to poverty has brought about a proposition by CK Prahalad which is termed the ‘Bottom of the pyramid proposition’ (BOP), which argues that low income markets present prodigious opportunity for Multinationals to profit by bringing prosperity to the aspiring poor. The main objective of the BOP proposition is for business as creators of wealth to make substantial inroads on the social challenges that confront societies while at the same time earning financial rewards. The problem of shareholder primacy has been cited as the Achilles heel for businesses when contemplating serving other stakeholders and society at large. This thesis sought to investigate the association between the shareholder primacy and the BOP market. In theoretical support of the shareholder primacy represented by the shareholder power and legitimacy of their interest, shareholder activeness within the business and the short-termism of those interests having a pernicious relationship with other stakeholders and society at large. Questionnaires were distributed to South African Business School students who are a closer approximation of business managers. The study achieved a turnover of 160 questionnaires with usable responses of 148 questionnaires. The statistical correlation was used to find an existence of relationship and simple regression analysis was used to test the hypotheses. The data shows that prioritization of shareholder power and legitimacy of their interest may lead to increased non-service of the BOP market. The verdict on shareholder activeness and short-term shareholder interest is inconclusive. However, directions for future research are given. These results suggest that all actors, such as Multinational corporations, business managers, researchers, management education, policy makers and government should be genuinely frustrated by issues that affect society and radically shift their mindset in viewing poverty as another opportunity to reconfigure their role in society and to the poor who are in the BOP market.
Thesis (M.M. (Entrepreneurship and New Venture Creation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2014